Lionel Groulx et l'esprit du libéralisme - Boily, Frédéric (Recherches sociographiques, 2004)
Number: 2
Keywords: Groulx; Lionel; Libéralisme

Le libéralisme dans la pensée religieuse de Mgr Bruchési - Primeau, Francis (Mens, 2007)
issued: 2007-21-00
Keywords: Bruchési; Paul; Libéralisme; Évêques

Libéralisme, nationalisme et catholicisme dans la pensée politique de Claude Ryan au Devoir (1962-1978) - Marcil, Olivier (Université de Montréal, 2001)
Keywords: Devoir (Le); Idéologies; Libéralisme; Nationalisme; Ryan; Claude

La raison et l'équilibre: libéralisme, nationalisme et catholicisme dans la pensée de Claude Ryan au Devoir, 1962-1978 - Marcil, Olivier (Varia, 2002)
Keywords: Devoir (Le); Idéologies; Libéralisme; Nationalisme; Ryan; Claude

Joséphine Marchand-Dandurand ou "Le Laurier féminin". Une journaliste féministe, moderne, libérale et nationaliste (1861-1925) - Doucet, Sophie (Université de Montréal, 2004)
Keywords: Journalistes; Marchand-Dandurand; Joséphine

La question linguistique dans la pensée de Claude Ryan au Devoir (1962-1978): la difficile conciliation de principes nationalistes et libéraux - Marcil, Olivier (Mens, 2002)
issued: 2002-21-00
Keywords: Anglophones; Devoir (Le); Francophones; Langue; Ryan; Claude

Manly Smokes: Tobacco Consumption and the Construction of Identities in Industrial Montreal, 1888-1914 - Rudy, Robert Jarrett (Université McGill, 2001)
This dissertation explores the cultural practice of smoking and its connection to social relations from the beginning of cigarette mass production in Montreal in 1888 to the First World War. It uncovers the norms of smoking etiquette and taste, their roots in gender, class and race relations and their use in reproducing these power relationships. It argues that these prescriptions reflected and served to legitimize beliefs about inclusion, exclusion and hierarchy that were at the core of nineteenth century liberalism. Liberal ideals of self-control and rationality structured the ritual of smoking: from the purchase of tobacco; to who was to smoke; to how one was supposed to smoke; to where one smoked. These prescriptions served to normalize the exclusion of women from the definition of the liberal individual and to justify the subordination of the poor and cultural minorities. Furthermore, even while these prescriptions were at their height, an emergent group of beliefs began to recast notions of respectable smoking around new ideals of speed and ungendered universality. This challenge was not only part of the transition from bourgeois to mass consumption, it was the roots of a transformation of the liberal order in the years previous to the First World War.
Keywords: Tabac

Conflict in Cities and the Struggle for Modernity. Toward an Understanding of the Spatiality of the October Crisis - Burke, Jason R. (Cahiers de géographie du Québec, 2009)
À partir des années 1960, le Québec était prêt pour le changement. Au cours de cette décennie, deux visions pour un Québec moderne prirent forme et s'affrontèrent, culminant par ce qui est connu comme la rencontre la plus significative du Canada avec le terrorisme, la Crise d'octobre. Pendant que le gouvernement libéral nouvellement élu poussait en avant des réformes sociales et économiques, le Front de libération du Québec (FLQ) émergeait avec une vision différente pour le Québec caractérisé par l'indépendance et le socialisme. Cet article soutient que la modernisation est presque toujours accompagnée de transformations géographiques et de violence. Il examine les implications spatiales de la violence du FLQ pendant les années 1960 et les réponses gouvernementales à la Crise d'octobre afin de fournir une nouvelle compréhension de cette crise. By the 1960s, Quebec was poised for change. Two visions of a modern Quebec began to emerge that clashed throughout the decade, culminating in what has become known as Canada's most significant encounter with terrorism: the October Crisis. While the newly elected Liberal government pushed forward with social and economic reforms, the Front de Libération du Québec (FLQ) emerged with a different vision for Quebec characterized by independence and socialism. This article argues that with modernization comes geographical transformation and violence. It looks at the spatial implications of FLQ violence during the 1960s and the government's response to the October Crisis as an attempt to provide a new understanding of the crisis.
Number: 150
Keywords: Crise d'octobre